TRANSCENDENT (Transforming Research by Assessing Neuroinformatics across the Spectrum of Concussion by Embedding iNterdisciplinary Data-collection to Enable Novel Treatments): protocol for a prospective observational cohort study of concussion patients with embedded comparative effectiveness research within a network of learning health system concussion clinics in Canada - Charlotte Anderson; Nick Reed; Andrée-Anne Ledoux; Roger Zemek; Keith Yeates; Carolyn Emery; Pamela Fuselli; Isabelle J Gagnon; Kathryn J Schneider; Sharon Johnston; David R Howell; Richard Webster; et al. (BMJ Open)
Introduction Concussion affects over 400 000 Canadians annually, with a range of causes and impacts on health-related quality of life. Research to date has disproportionately focused on athletes, military personnel and level I trauma centre patients, and may not be applicable to the broader community. The TRANSCENDENT Concussion Research Program aims to address patient- and clinician-identified research priorities, through the integration of clinical data from patients of all ages and injury mechanisms, patient-reported outcomes and objective biomarkers across factors of intersectionality. Seeking guidance from our Community Advisory Committee will ensure meaningful patient partnership and research findings that are relevant to the wider concussion community.Methods and analysis This prospective observational cohort study will recruit 5500 participants over 5 years from three 360 Concussion Care clinic locations across Ontario, Canada, with a subset of participants enrolling in specific objective assessments including testing of autonomic function, exercise tolerance, vision, advanced neuroimaging and fluid biomarkers. Analysis will be predicated on pre-specified research questions, and data shared with the Ontario Brain Institute’s Brain-CODE database. This work will represent one of the largest concussion databases to date, and by sharing it, we will advance the field of concussion and prevent siloing within brain health research.Ethics and dissemination This study was approved by the Children’s Hospital of Eastern Ontario Research Ethics Board and preregistered on OSF (25 June 2024); https://doi.org/10.17605/OSF.IO/HYDZC. Dissemination of findings will be multifaceted, including conference presentations, peer-reviewed publications and sharing of adapted materials (eg, videos, infographics, plain language summaries) with community groups and key knowledge users.